Loading of praziquantel in the crystal lattice of solid lipid nanoparticles Studies by DSC and SAXS - Ribeiro de Souza, Ana Luiza [UNESP]; Andreani, Tatiana; Nunes, Fernando M.; Cassimiro, Douglas Lopes [UNESP]; de Almeida, Adelia Emilia [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Vitorino Sarmento, Victor Hugo; Daflon Gremiao, Maria Palmira [UNESP]; Silva, Amelia M.; Souto, Eliana B. (Springer, 2012)
Praziquantel (PZQ) is the drug of choice for oral treatment of schistosomiasis and other fluke infections that affect humans. Its low oral bioavailability demands the development of innovative strategies to overcome the first pass metabolism. In this article, solid lipid nanoparticles loaded with PZQ (PZQ-SLN) were prepared by a modified oil-in-water microemulsion method selecting stearic acid as lipid phase after solubility screening studies. The mean particle size (Z-Ave) and zeta potential (ZP) were 500 nm and -34.0 mV, respectively. Morphology and shape of PZQ-SLN were analysed by scanning electron microscopy revealing the presence of spherical particles with smooth surface. Differential scanning calorimetry suggested that SLN comprised a less ordered arrangement of crystals and the drug was molecularly dispersed in the lipid matrix. No supercooled melts were detected. The entrapment efficiency (EE) and loading capacity of PZQ, determined by high performance liquid chromatography, were 99.06 +/- 0.3 and 17.48 +/- 0.05, respectively. Effective incorporation of PZQ into the particles was confirmed by small angle X-ray scattering revealing the presence of a lipid lamellar structure. Stability parameters of PZQ-SLN stored at room temperature (25 degrees C) and at 4 degrees C were checked by analysing Z-Ave, ZP and the EE for a period of 60 days. Results showed a relatively long-term physical stability after storage at 4 degrees C, without drug expulsion.
Keywords: Solid lipid nanoparticles; Praziquantel; Differential scanning calorimetry; Scanning electron microscopy; Photon correlation spectroscopy; Modified oil-in-water microemulsion; High-shear homogenization